A new method of collecting water from an external hydrant in the event of large-scale power failures - Szpak, Dawid; Różańska, Aleksandra (Instal, 2024)
The water supply system should be prepared to function both in normal conditions and in a crisis situation. A large-scale power failure may limit or completely stop the operation of water supply systems. For this reason, blackout is considered one of the greatest threats to the continuity of the supply of drinking water. The study assessed the preparation of a water supply company for water supply in a crisis situation based on conventional solutions. The idea of an original solution for drawing water from the water supply network during low pressure was presented. The developed water tap allows the use of water accumulated in water pipes by drawing it from external hydrants. The method of arranging draw-off points in the water supply network is presented. The accumulated amounts of water inside water pipes can provide significant support for the affected population during periods of lack of electricity supply, preventing the operation of water pumping stations. Obtaining treated water and distributing it among residents will reduce the health risks associated with the consumption of water of uncertain origin.
Keywords: crisis situation; external hydrant; lack of water; water supply system